Chronic pesticide mixture exposure including paraquat and respiratory outcomes among colombian farmers (2020)
This study explored the potential association between chronic exposure to pesticide mixtures including paraquat and respiratory outcomes among Colombian farmers. Sociodemographic and occupational data, respiratory symptoms and spirometric data were collected. Paraquat in spot urine samples were quantified with solid-phase extraction high-performance liquid chromatography. Multiple Poisson regressions with robust variance were used to determine factors associated with respiratory outcomes. Profiles of pesticide mixtures used were identified among 217 farmwork-ers, but profenofos and methamidophos-based mixtures were more frequent. Chronic paraquat exposure was slightly associated with self-reported asthma (PR: 1.06; 95% CI 1.00 to 1.13). Different pesticide mixtures were associated with flu, thoracic pain, allergic rhinitis, and obstructive pattern in spirometry. Although acute exposure to paraquat is low among Colombian farmers participating in the study, associations between respiratory outcomes and chronic pesticide mixtures exposure including profenofos, methamidophos or glyphosate require further specific studies. © 2020 National Institute of Occupational Safety and Health.